2020
DOI: 10.2196/15815
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Feasibility, and Patient Acceptance of an Electronic Version of a Multidimensional Health Assessment Questionnaire for Routine Rheumatology Care: Validation and Patient Preference Study

Abstract: Background A multidimensional health assessment questionnaire (MDHAQ) that was developed primarily for routine rheumatology care has advanced clinical research concerning disease burden, disability, and mortality in rheumatic diseases. Routine Assessment of Patient Index Data 3 (RAPID3), an index within the MDHAQ, is the most widely used index to assess rheumatoid arthritis (RA) in clinical care in the United States, and it recognizes clinical status changes in all studied rheumatic diseases. MDHAQ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Digital eMDHAQ versions have been developed for patient completion at home, any clinical setting, or anywhere the internet is available to report current clinical status and possible intercurrent problems such as disease flares, adverse effects of medications, or new comorbidities [15,76]. Analyses of the eMDHAQ versus a paper version in 98 patients indicated that mean levels of 4 individual scores and 3 indices were all within 2%, with intraclass correlation coefficients of 0.86-0.98 (Table 3) [15]. Among 98 patients, 72% expressed a preference for an eMDHAQ, compared to 7% for the paper version, while 21% expressed no preference [15].…”
Section: A Digital Emdhaqmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital eMDHAQ versions have been developed for patient completion at home, any clinical setting, or anywhere the internet is available to report current clinical status and possible intercurrent problems such as disease flares, adverse effects of medications, or new comorbidities [15,76]. Analyses of the eMDHAQ versus a paper version in 98 patients indicated that mean levels of 4 individual scores and 3 indices were all within 2%, with intraclass correlation coefficients of 0.86-0.98 (Table 3) [15]. Among 98 patients, 72% expressed a preference for an eMDHAQ, compared to 7% for the paper version, while 21% expressed no preference [15].…”
Section: A Digital Emdhaqmentioning
confidence: 99%
“…Analyses of the eMDHAQ versus a paper version in 98 patients indicated that mean levels of 4 individual scores and 3 indices were all within 2%, with intraclass correlation coefficients of 0.86-0.98 (Table 3) [15]. Among 98 patients, 72% expressed a preference for an eMDHAQ, compared to 7% for the paper version, while 21% expressed no preference [15]. The eMDHAQ is secure and HIPAA-compliant [15] and includes the capacity to interface with any EMR through the HL 7 FHIR standard [77], but implementation into routine care has not been possible to date, as discussed in further detail below.…”
Section: A Digital Emdhaqmentioning
confidence: 99%
See 1 more Smart Citation
“…It is non‐proprietary for clinical use, takes 5–10 seconds to complete and does not require extra clinic time or physician training 30 . It was designed for use in clinical practice, as opposed to use in the clinical trial setting and can be easily electronically administered 37 …”
Section: Discussionmentioning
confidence: 99%
“…35 PROMS have the potential to facilitate shared decision making, guide patient-physician communication and provide feedback for progress over time. 36,37 Second, the application of PROMs in settings independent of traditional appointments presents a promising opportunity to empower patients. In a recent pilot study employing online self-monitoring in patients with inflammatory arthritis, patients reported increased knowledge and awareness of their disease, with some noting earlier self-recognition of disease flare.…”
Section: Ta B L E 3 Receiver Operating Characteristic Curve Outputmentioning
confidence: 99%